PENERAPAN TEKNOLOGI AUTOMATIC RIVER CLEANER (ARC) SEBAGAI UPAYA MEWUJUDKAN DESTINASI WISATA KOTA (CITY TOUR) DI BANYUWANGI: Applied Of Automatic River Cleaner (ARC) Technology to Create A City Tourism Destination In Banyuwangi - Haq, Endi Sailul; Utomo, Agus Priyo; Prayogo, Galang Sandy; Pranowo, Dadang Dwi (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2024)
Sumber Seng River is a river in the heart of Banyuwangi. The flow of this river starts from a spring located right in the middle of the city. During the rainy season, the rainwater that flows in the river carries a lot of leaves and plastic waste material. The garbage does not come from the surrounding community, but outside areas carried away by rainwater entering the Sumber Seng River flow. Garbage carried by water will usually close the river barrier, deliberately made to increase the water discharge. When it is covered with garbage, the problem arises because the flow of rainwater is not smooth, so there is a risk of overflow and flooding. For this reason, this Automatic River Cleaner (ARC) Technology can take garbage and collect garbage in the provided place effectively. This system will run automatically with the esp8266 microcontroller equipped with a waterproof ultrasonic sensor, a floating switch to detect water levels, and a power source with a solar panel to operate when a power outage occurs. Residents can get information on water level, condition of equipment functioning or not, and control to stop or turn on equipment remotely through the telegram application